Learners’ perspective on critical factors to cloud VLE success: an empirical investigation - Kassim, Rahimah; Abdul Hamid, Nor Aziati; H.B, Adnan; N, Latipah; A, Maizurah (Science Publishing Corporation (SPC), 2018)
The use of Virtual Learning Environment (VLE) in academic institutions is becoming an imperative for many institutions. The growth of the advanced education system now is depending on the increased of Virtual Learning Environment (VLE) technology utilization. Education institution communities are encouraged to adopt a variety of VLE technology to support the process of teaching and learning. The objective of this research is to measure perspective of VLE acceptance among lecturers in the context of Moodle application by using data from 541 lecturers at selected Higher Education Institutions. A framework of research constructed based on a comprehensive study on the theory of service quality and the Technology Acceptance Model (TAM). Eight factors hypothesized which consist of five independent variables; organization support, knowledge support, technical assistance, system characteristics and lecturer style and innovation, two belief variables; perceived usefulness and perceived ease of use and one dependent variable; behavioral intention to use the VLE. All the factors were tested to determine whether they are important in influencing future use of the VLE and statistical analysis methods determined the key driving factors. Results of regression analysis showed that university lecturers have an above average level of VLE acceptance with the very high level of significant value.